PERANCANGAN MEDIA BUKLET SOSIALISASI BKMM MENGENAI KESEHATAN MATA ANAK DI SUMATERA BARAT - Hikmah Hasmaini; Erwin .; Jamilus . (DEKAVE : Jurnal Desain Komunikasi Visual, 2012)
AbstractPurpose of this final work is (1) The design of the booklet as a medium of Balai Kesehatan Mata Masyarakat (BKMM) that discussed the eye health of children in West Sumatra, both verbally and visually (2) Designing an image that is comical, to determine the color, typography, layout communicative to the child so that it has its own characteristics. The source of this final work is primary data which information obtained from interviews with cadres and employees of Balai Kesehatan Mata Masyarakat (BKMM), secondary data obtained from several sources discussing public service ads. Final work in the form of communicative booklets for children in which there are images that are comical, color, typography, layout and language tailored to the child's verbalKeyword: perancangan, buklet, Iklan Layanan Masyarakat, BKMM, Sumatera Barat.